PRODUKTIVITAS PENYADAPAN GETAH PINUS (PINUS MERKUSII JUNGH) DI LPHN SIMARASOK KECAMATAN BASO KABUPATEN AGAM PROVINSI SUMATERA BARAT - Susilastri, Susilastri; Husnul Fadhli, Muhammad; Fakhruzy, Fakhruzy (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Pine trees that are still productive will produce sap, pine resin is one of the non-timber forest products commodities that is quite potential and Indonesia has the 3rd largest production in the worldThis study aims to determine the productivity of pine resin and aspects that meet standard operating procedure criteria for pine trees (Pinus merkusii) in the Nagari Simarasok forest area, Baso District, Agam Regency, West Sumatra Province. The data collected was in the form of primary data and data collection was carried out by observation, measurement, line transect, sample plots (plots), and literature study and then analyzed using quantitative descriptive and qualitative descriptive methods. The results showed that the diameter of the tapped pine in the Nagari Simarasok forest, Baso District, Agam Regency, West Sumatra Province varied between 32–83 cm with an average diameter of 62.84 cm with pine resin productivity per tree ranging from 90–266 grams/tree per day with the average pine resin is 194.72 grams/tree per day. The productivity of pine resin per type is between 29.9–45 grams/typing per day with an average pine resin of 32.87 grams/typing per day. The results of data collection regarding standard operating procedures on pine trees were 13 out of 144 pine trees that did not meet the criteria, where 1 stem had a depth Keywords: Resin, Productivity, Nagariforest, SOP